The Students’ Perception on Reward Toward Their Motivation in English Learning - Taufik, Wildan As'at; Siregar, Fitri Rayani; Rambe, Sokhira Linda Vinde (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This research was aimed to find out students' perceptions on reward toward their motivation in learning English. This research used qualitative research with descriptive method. The subjects of this study were students of class X IPA and The English teacher at MAS Ponpes NU Paringgonan Padang Lawas. Questionnaires and interviews were used to collect data. The results of this study is from the five kinds of reward in English learning at MAS Ponpes NU Paringgonan Padang Lawas teacher often uses four types: Giving number or value, Giving gift, Rewarding/attention, and Praise but the most dominant one is Giving a number or value.